BIOMedical search engine framework: lightweight and customized implementation of domain-specific biomedical search engines - Jácome, Alberto G. (2016)
The Smart Drug Search is publicly accessible at http://sing.ei.uvigo.es/sds/. The BIOMedical Search Engine Framework is freely available for non-commercial use at https://github.com/agjacome/biomsef